A terceirização no trabalho bancário: implicações materiais e simbólicas - CARVALHO, Josué Pires de (2006)
The study aims to discuss the outsourcing process marked by the call restructuring process that began around the last quarter of the twentieth century. Thus, from the cooling process of accumulation Fordist / Keynesian Concomitant with the development of flexible forms of production sustained in revival of liberalism, we seek to understand the socioeconomic context in which outsourcing takes place, and then investigate their impact on social relations work in order that the use of outsourcing is a strategy flexible organization of production and work. The attention to the fact that in the midst of capitalist restructuring turns out a significant growth services sector (including in relation to the absorption of manpower) over a relative shrinkage in the agricultural and industrial sectors, directs the focus of empirical research for the "production" of services, especially in the subsector banking. Moreover, this approach is due to some lack of studies on the sector services in Brazil, by the sociology and economics work. Part empirical occurred through conducting a case study in a bank official which houses workers on staff and outsource its dependencies. The survey results point to aspects such as: fragmentation union representation, identity conflicts between contractors and banks, upward immobility of outsourcing, wage reductions of direct and indirect workers, contractors who develop end-activities of the acquiring bank, weakening of the employment relationship and so on. Regarding the theoretical foundation, the study is guided by the notions of productive restructuring; "capital symbolic ", elaborated by Bourdieu, of" regulated citizenship "discussed by Wanderley Guilherme dos Santos; "new social question", discussed by Castel; work identities from the perspective of Claude Dubar